Zearalenone Exposure Enhanced the Expression of Tumorigenesis Genes in Donkey Granulosa Cells via the PTEN/PI3K/AKT Signaling Pathway - Zhang, Guo-Liang; Song, Jun-Lin; Ji, Chuan-Liang; Feng, Yu-Long; Yu, Jie; Nyachoti, Charles M.; Yang, Gong-She (Frontiers in Genetics, 2018)
Zearalenone (ZEA) is a natural contaminant existing in food and feed products that exhibits a negative effect on domestic animals’ reproduction. Donkeys possess high economic value in China and are at risk of exposure to ZEA. However, few information is available on ZEA-induced toxicity and no report on toxicity in donkeys can be found in scientific literature. We investigated the biological effects of ZEA exposure on donkey granulosa cells (dGCs) by using RNA-seq analysis. ZEA at 10 and 30 μM were administered to GCs within 72 h of in vitro culture. ZEA at 10 μM significantly altered the tumorigenesis associated genes in dGCs. Exposure to 10 and 30 μM ZEA treatment significantly reduced mRNA expression of PTEN, TGFβ, ATM, and CDK2 genes, particularly, the ZEA treatment significantly increased the expression of PI3K and AKT genes. Furthermore, immunofluorescence, RT-qPCR, and Western blot analysis verified the gene expression of ZEA-exposed GCs. Collectively, these results demonstrated the deleterious effect of ZEA exposure on the induction of ovarian cancer related genes via the PTEN/PI3K/AKT signaling pathway in dGCs in vitro.